Numerical modeling of composite beam to reinforced concrete wall joints : part II : global behavior - Henriques, José (2013)
The research leading to these results has recieved funding from the European Community’s Research Fund for Coal and Steel (RFCS) under grant agreement no. RFSR-CT-2007-00051.